Characterization of the fruit proteolytic system of Bromelia serra Griseb. (Bromeliaceae) and its application in bioactive peptides release - Salese, Lucía (2022)
A crude extract with proteolytic activity was prepared from edible fruits of Bromelia serra, containing cysteine peptidases with molecular masses between 24.1 and 25.9 kDa. The extract presented an optimal pH range of 6.03‒9.05, retained more than 80% of activity after thermal pre-treatments at 23, 37, and 45°C (120 min), but it was rapidly inactivated after 10 min at 75°C. These proteases were employed to hydrolyze soybean proteins, bovine casein and bovine whey, achieving degrees of hydrolysis of 18.3 ± 0.6, 29.1 ± 0.7, and 12.6 ± 0.9% (55°C, 180 min), respectively. The casein 180 min-hydrolysate (55°C) presented the maximum value of antioxidant activity (2.89 ± 0.12 mg/mL Trolox), and the whey protein 180 min-hydrolysate (55°C) showed the highest percentage of angiotensin-converting enzyme inhibition (91.9 ± 1.2%). This low-cost enzymatic preparation would be promising for the food industry because it requires mild working conditions and yields hydrolysates with biological activities useful as ingredients for functional food.